2004
DOI: 10.3141/1875-01
|View full text |Cite
|
Sign up to set email alerts
|

Essential and Plastic Works of Ductile Fracture in Asphalt Binders

Abstract: Currently, no satisfactory asphalt binder test method exists that can relate properties measured in the laboratory to fatigue performance in service. The loss modulus of the binder, G*sinδ, as proposed by the Strategic Highway Research Program, is a rheological parameter that measures the energy dissipated within the homogeneous binder at low strains under dynamic conditions. A number of publications have reported that this binder parameter provides little correlation with the susceptibility of the asphalt con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(34 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…These damaging conditions are normally accompanied by high strain levels and yielding in binder films in the nonlinear viscoelastic range. In response to that, researchers at Queen's University proposed the double-edged notched tension (DENT) test which is based on the concept of essential work of fracture (EWF) of materials in a ductile state [39]. The binder ranking based on this method showed a strong correlation with observed fatigue cracking in the accelerated loading facility (ALF) and exactly the same ranking as the push-pull asphalt mix fatigue test [18,19].…”
Section: Time-temperature Superposition Principle (Ttsp)mentioning
confidence: 99%
See 3 more Smart Citations
“…These damaging conditions are normally accompanied by high strain levels and yielding in binder films in the nonlinear viscoelastic range. In response to that, researchers at Queen's University proposed the double-edged notched tension (DENT) test which is based on the concept of essential work of fracture (EWF) of materials in a ductile state [39]. The binder ranking based on this method showed a strong correlation with observed fatigue cracking in the accelerated loading facility (ALF) and exactly the same ranking as the push-pull asphalt mix fatigue test [18,19].…”
Section: Time-temperature Superposition Principle (Ttsp)mentioning
confidence: 99%
“…Andriescu et al [39] successfully applied this test on bituminous binders. They found that no correlation exists between fracture properties and the SHRP fatigue parameter.…”
Section: Essential Work Of Fracture (Ewf) Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the fatigue life of hot-mix asphalt (HMA) has been recognized to be highly sensitive to the properties of the binder and fatigue cracking normally initiates and propagates within the binder, binder-filler mastic or at the bitumen-aggregate interface. A large number of research groups have attempted to identify testing procedures and fundamental parameters that can accurately reflect the contribution of the binders' properties on the fatigue resistance of asphalt mixtures and subsequent pavement performance [2][3][4][5][6][7][8][9][10][11]. In this regard, time sweep repeated cyclic loading tests, adopted in this study, have been successfully used to evaluate the fatigue properties of binders [3,5,12].…”
Section: Introductionmentioning
confidence: 99%